2021
DOI: 10.3390/jcm10020323
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of Chronic Heart Failure and Utility of NT-proBNP Levels in Heart Failure Patients with SARS-CoV-2 Infection

Abstract: Background: The prevalence and prognostic value of chronic heart failure (CHF) in the setting of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection has seldom been studied. The aim of this study was to analyze the prevalence and prognosis of CHF in this setting. Methods: This single-center study included 829 consecutive patients with SARS-CoV-2 infection from February to April 2020. Patients with a previous history of CHF were matched 1:2 for age and sex. We analyze the prognostic value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 41 publications
2
26
1
2
Order By: Relevance
“…Thirty-two studies were conducted in Asia ( 7 , 22 , 24 , 26 , 27 , 29 , 31 33 , 35 , 38 46 , 48 , 50 , 51 , 53 55 , 57 63 ), eight in Europe ( 25 , 28 , 30 , 34 , 47 , 49 , 52 , 56 ), three in America ( 23 , 36 , 37 ), and one in Africa ( 21 ). Thirty-two studies were retrospective ( 7 , 21 23 , 27 , 29 , 31 39 , 41 45 , 48 , 50 , 51 , 53 , 55 , 57 63 ), eight prospective ( 24 , 30 , 46 , 47 , 49 , 52 , 54 , 56 ), whereas the remaining four did not report the study design ( 25 , 26 , 28 , 40 ). Clinical endpoints included disease severity based on current clinical guidelines in 15 studies ( 21 , 24 , 33 , 39 41 , 43 , 48 , 54 , 55 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-two studies were conducted in Asia ( 7 , 22 , 24 , 26 , 27 , 29 , 31 33 , 35 , 38 46 , 48 , 50 , 51 , 53 55 , 57 63 ), eight in Europe ( 25 , 28 , 30 , 34 , 47 , 49 , 52 , 56 ), three in America ( 23 , 36 , 37 ), and one in Africa ( 21 ). Thirty-two studies were retrospective ( 7 , 21 23 , 27 , 29 , 31 39 , 41 45 , 48 , 50 , 51 , 53 , 55 , 57 63 ), eight prospective ( 24 , 30 , 46 , 47 , 49 , 52 , 54 , 56 ), whereas the remaining four did not report the study design ( 25 , 26 , 28 , 40 ). Clinical endpoints included disease severity based on current clinical guidelines in 15 studies ( 21 , 24 , 33 , 39 41 , 43 , 48 , 54 , 55 ,…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-two studies were retrospective ( 7 , 21 23 , 27 , 29 , 31 39 , 41 45 , 48 , 50 , 51 , 53 , 55 , 57 63 ), eight prospective ( 24 , 30 , 46 , 47 , 49 , 52 , 54 , 56 ), whereas the remaining four did not report the study design ( 25 , 26 , 28 , 40 ). Clinical endpoints included disease severity based on current clinical guidelines in 15 studies ( 21 , 24 , 33 , 39 41 , 43 , 48 , 54 , 55 , 57 59 , 62 , 63 ), hospitalization in one ( 37 ), ICU transfer in three ( 32 , 44 , 49 ), or need for mechanical ventilation in one ( 23 ), and survival status in 24 studies ( 7 , 22 , 25 31 , 34 36 , 38 , 42 , 45 47 , 50 53 , 56 , 60 , 61 ). Sixteen studies reported plasma BNP concentrations ( 23 , 24 , 26 , 33 , 35 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tornero et al published a study focusing on chronic heart failure (CHF) and SARS-CoV-2 with interesting results [41]. They reported a significant increase in mortality in patients with CHF (n=43) and in this population, the mortality was associated with hs-TnT, but not NT-proBNP.…”
Section: Comorbiditiesmentioning
confidence: 98%
“…NT-proBNP is an independent risk factor for negative outcomes and in clinical practice it could be used in conjunction with troponins, to detect patients with poor prognosis [31]. The proposed cut-off values for NT-proBNP in current literature are 88.64 pg/mL with a sensitivity 100% and specificity 67% for predicting in-hospital death and in the CHF subgroup 2598 pg/ml (sensitivity 91.7%, specificity 80%) [41,56]. In order to achieve more reliable prognosis in SARS-CoV-2 infection, further research should establish different cut-off values according to the patients' age, as is the norm for NT-proBNP.…”
Section: Natriuretic Peptidesmentioning
confidence: 99%